DESCARTES ABOUT ANTHROPOLOGICAL GROUNDS OF PHILOSOPHY IN THE "EARLY WRITINGS" - А. М. Маlivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of this work is to find the key to understanding the paradox of Descartes’ way of philosophizing during the recourse to the text of "early writings". Realization of the set purpose involves the consistent solving of such tasks: by referring to the research literature, to outline the forms of transition to modern methodology; to explicate the main reasons for philosophy anthropologization by Descartes; to analyze the role of art as the main form of expressing Descartes’ worldview in the "early writings". Theoretical basis. Studies by Descartes experts and the phenomenological tradition. Originality. The analysis of the "early writings" allows to determine the origins of the main doctrine of Descartes’ philosophizing. Its role is manifested in the course of clarifying the main motives of the anthropological approach of the French philosopher. That entails their rootedness in the Copernican-based scientific revolution of the New Age. A prerequisite for the authentic comprehension of the radical change carried out by Descartes is the attention to the paradigmatic significance of art, which is most fully asserted in the "early writings". It is substantiated that the appeal of young Descartes to the experience of art influences his understanding of science, as well as the awareness of human presence in the development of the scientific picture of the world and the distinction of the main components of human nature – mind and will. Conclusions. During the analysis of the contemporary literature devoted to Descartes, there is outlined the tendency to go beyond the notions of naivety and simplicity of his position, one of the manifestations of which is the increased attention to anthropology. The main motives for its actualization are rooted in the scientific revolution of the New Age, which are the form of completion of the radical worldview change initiated by Copernicus. It is about the vision of man as the main component of the universe, attention thereto in the search for the source point and the decisive authority for the world development, reflection of the thinker’s desire to build his own ethical doctrine based on human nature. While comprehending the "early wri-tings", the author focuses on the interpretation by young Descartes of art as a form of expression of truth, which enables the authentic comprehension of human nature. These ideas became the basis for the further work of the thinker, and today they open up new perspectives of exploring the anthropological foundation for later works.